the The Effectiveness of Using Ecoenzymes Based on Several Kinds of Fruit on the Growth of Lettuce (Lactuca sativa L.) - Yunita dondo; Tommy D. Sondakh; Ronny Nangoi (Jurnal Agroekoteknologi Terapan, 2023)
This study aims to determine the effectiveness of ecoenzymes from various basic ingredients of fruit peels on the growth of lettuce (Lactuca Sativa L). This study used a completely randomized design (CRD) consisting of 6 treatments 3 replications, so there were 18 experimental unit parameters namely number of leaves, fresh weight and root weight. Observational data were analyzed statistically which were then further tested for BNT (smallest significant difference) at the 5% level.The results of the research that has been done can be concluded that the use of ecoenzymes from several kinds of fruit is effective for the growth of lettuca plants. The ecoenzyme concentration of several kinds of fruit used is 3% (30ml/1000 ml water). Keywords:  ecoenzymes,  Lactuca Sativa L, plant growth Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas ekoenzim dari berbagai bahan dasar kulit buah terhadap pertumbuhan tanaman selada (Lactuca Sativa L). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari 6 perlakuan 3 ulangan, sehingga terdapat 18 parameter satuan percobaan yaitu jumlah daun, bobot segar dan bobot akar. Data pengamatan dianalisis secara statistik yang selanjutnya diuji BNT (beda nyata terkecil) pada taraf 5%. Hasil penelitian yang telah dilakukan dapat disimpulkan bahwa penggunaan ekoenzim dari beberapa jenis buah efektif untuk pertumbuhan tanaman selada. Konsentrasi ekoenzim beberapa jenis buah yang digunakan adalah 3% (30ml/1000ml air). Kata kunci:  ecoenzymes,  Lactuca Sativa L,  pertumbuhan tanaman